PENGALAMAN SUAMI DALAM PERSPEKTIF SOCIAL CULTURE TERHADAP DUKUNGAN PEMBERIAN ASI: STUDI KUALITATIF - Nurvitriana, Nidya Comdeca; Arista, Devi Maya (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: Breast milk is the optimal source of nutrition for infants. The provision of exclusive breastfeeding can be influenced by various factors, including the support of the husband. This study aims to explore the experiences of husbands in supporting exclusive breastfeeding from a socio-cultural perspective. Using a qualitative approach, the study involved semi-structured interviews with 10 participants who were husbands of mothers with infants aged 0-6 months. The data collected were analyzed using Atlas.ti 9.0 software with a thematic analysis approach. Three main themes emerged from the analysis: the husband's role in breastfeeding preparation during pregnancy, direct emotional support from the husband, and the husband's readiness to assist in the breastfeeding process. The findings of this study suggest that the active involvement of husbands in supporting mothers, both emotionally, practically, and in preparing for breastfeeding, significantly influences the success of exclusive breastfeeding. The study recommends increasing social awareness to promote the involvement of husbands in supporting the successful implementation of exclusive breastfeeding.Keywords: Breastfeeding, fathers, qualitative study